Cancer Cell B7-H3 Expression Is More Prevalent in the Pancreato-Biliary Subtype of Ampullary Cancer Than in Pancreatic Cancer - Geerdes, Emma E.; Sideras, Kostandinos; Aziz, M. Hosein; van Eijck, Casper H.; Bruno, Marco J.; Sprengers, Dave; Boor, Patrick P. C.; Kwekkeboom, Jaap (Frontiers in Oncology, 2021)
B7-H3 is an immunomodulatory member of the B7-superfamily with limited expression in normal tissues, but overexpression in several types of cancer. Therefore it is currently being explored as a potential target for cancer immunotherapy. The biological relevance of B7-H3 expression in pancreatic cancer is unclear, while there are no data on B7-H3 expression in ampullary cancer. We aimed to compare intra-tumoral B7-H3 expression between these two closely related cancer types and analyze its association with post-surgical disease course. B7-H3 expression levels were determined by immunohistochemistry in tissue microarrays of resected tumors of 137 pancreatic cancer patients and 83 patients with ampullary cancer of the pancreato-biliary subtype. B7-H3 was more frequently expressed in cancer cells of ampullary cancer patients compared to pancreatic cancer patients (51% versus 21%; p< 0.001). In ampullary cancer patients, but not in pancreatic cancer patients, B7-H3 cancer cell expression was associated with longer disease-free survival and patient survival. However, the prognostic value of B7-H3 was lost upon adjustment for CA19-9 levels. The frequencies of B7-H3 expression in tumor stroma did not differ between the two types of cancer (66% versus 63%). In both cancer types, stromal B7-H3 expression was not associated with post-surgical disease course. Compared to pancreatic cancer, B7-H3 is more frequently expressed in cancer cells of patients with the pancreato-biliary subtype of ampullary cancer. These data suggest that B7-H3 may represent an interesting potential target for immunotherapy in ampullary cancer rather than in pancreatic cancer.